Targeted Financial Sanctions and the Evolving European Union AML/CFT Framework: What's Changing and Why It Matters - Georgios Pavlidis (Bratislava Law Review, 2025)
This paper aims to examine two recent legislative initiatives of the European Union (EU)-the 6th AML Directive and the new AML Regulation, focusing particularly on the provisions that reform targeted financial sanctions as part of the EU's anti-money laundering and countering the financing of terrorism (AML/CFT) framework. The paper explores why the reform was considered necessary, highlights the key objectives and rules governing targeted financial sanctions in the context AML/CFT, and discusses the challenges, as well as the opportunities that arise. The article argues that the integration of TFS into AMLD6 and AMLR represents more than a technical adjustment. It transforms sanctions from primarily foreign-policy tools into core preventive obligations embedded in the compliance frameworks of public authorities and private actors. This reorientation, however, raises challenges of consistency, resource allocation, and rights protection that will ultimately determine the effectiveness of the EU's new sanctions architecture.
Keywords: 330; European Union; Targeted Financial Sanctions; Money Laundering; AML